Fenómenos lineales y no lineales en la transmisión por fibra óptica - Cecilia Puerto López, Karla; Eliécer Galvis Velandia, Jorge; Leonardo Camargo Ariza, Luis (Editorial Unimagdalena, 2025)
Phenomena occurring in optical fibers affect the performance of communication systems. Understanding these behaviors aids in selecting the appropriate fiber type, optimizing fiber capacity, and mitigating adverse effects. For these reasons, this book provides a mathematical and conceptual analysis of the linear and nonlinear phenomena involved in fiber optic data transmission. The language is simple, with specific examples, and is supplemented by a free computational tool to expedite mathematical calculations and graphical representations.The book begins by introducing the reader to optical fiber types, the components of an optoelectronic system, the relevant electromagnetic spectrum, the nonlinear Schrödinger equation, and the Helmholtz equation. It then presents the application of geometrical optics in fiber, followed by a discussion on attenuation and dispersion within the framework of linear operation. Next, the focus shifts to nonlinear operation, including the Kerr effect, self-phase modulation, and third-order dispersion. Finally, four-wave mixing in a three-channel system is analyzed.